Representations of Childhood in American Modernism - Phillips, Michelle H.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book documents American modernism's efforts to disenchant adult and child readers alike of the essentialist view of childhood as redemptive, originary, and universal. For James, Barnes, Du Bois, and Stein, the twentieth century's move to position the child at the center of the self and society raised concerns about the shrinking value of maturity and prompted a critical response that imagined childhood and children's narratives in ways virtually antagonistic to both. In this original study, Michelle H. Phillips argues that American modernism's widespread critique of childhood led to some of the period's most meaningful and most misunderstood experiments with interiority, narration, and children's literature.
Introduction -- American Modernism, Childhood, and The Inward Turn -- The "Partagé Child" And The Emergence of The Modernist Novel in What Maisie Knew -- An Innocence Worse Than Evil in The Turn of The Screw -- Nightwood: A Bedtime Story -- The Children of Double Consciousness: From The Souls of Black Folk to The Brownies' Book -- Drowning In Childhood: Gertrude Stein's Late Modernism -- Works Cited .
Keywords: America-Literatures.; United States-History.; North American Literature